Clinical heterogeneity in lymphoedema-distichiasis withFOXC2 truncating mutations. Issue 11 (1st November 2001) - Erickson, Robert P; Dagenais, Susan L; Caulder, Mark S; Downs, Catherine A; Herman, Gail; Jones, Marilyn C; Kerstjens-Frederikse, Wilhelmina S; Lidral, Andrew C; McDonald, Marie; Nelson, Christine C; Witte, Marlys; Glover, Thomas W
Abstract : BACKGROUND: Hereditary lymphoedema-distichiasis (LD) is an autosomal dominant disorder that classically presents as lymphoedema of the limbs, with variable age of onset, and extra aberrant growth of eyelashes from the Meibomian gland (distichiasis). Other major reported complications include cardiac defects, cleft palate, and extradural cysts. Photophobia, exotropia, ptosis, congenital ectropion, and congenital cataracts are additional eye findings. Recently, we reported that truncating mutations in the forkhead transcription family member FOXC2 resulted in LD in two families. METHODS: The clinical findings in seven additional families with LD, including the original family described by Falls and Kertesz, were determined and mutational analyses were performed. RESULTS: Distichiasis was the most common clinical feature followed by age dependent lymphoedema. There is a wide variation of associated secondary features including tetralogy of Fallot and cleft palate. The mutational analyses identified truncating mutations in all of the families studied (two nonsense, one deletion, three insertion, and one insertion-deletion), which most likely result in haploinsufficiency of FOXC2 . CONCLUSIONS: FOXC2 mutations are highly penetrant with variable expressivity which is not explicable by the pattern of mutations.